Family Business Internationalization in Paradox: Effects of Socioemotional Wealth and Entrepreneurial Spirit - Jin, Chenfei; Wu, Bao; Hu, Yingjie (Frontiers in Psychology, 2021)
This study investigates internationalization (i.e., foreign investment) of small family business by classifying the effects of external socioemotional wealth (family reputation) versus internal socioemotional wealth (family involvement). Results using 2704 Chinese small family businesses support our hypothesis that family reputation has positive effect on internationalization, while family involvement has negative effect on internationalization. Moreover, entrepreneurial spirit reinforces the positive effect of family reputation on internationalization and enhance the negative relationship between family involvement and internationalization. This study contributes by examining the effect of entrepreneurial spirit as a potential balance factor for the paradoxical influences of internal versus external socio-emotional wealth.